NATIONAL POVERTY ERADICATION PROGRAMME (NAPEP) AND POVERTY ALLEVIATION IN RURAL NIGERIA: A CASE STUDY OF GIWA LOCAL GOVERNMENT AREA OF KADUNA STATE - Rahila Yakubu; Abbass I. M. (European Scientific Journal, ESJ, 2012)
The study aims at analyzing the framework of NAPEP inorder to ascertain the impact of the programme on the people of Giwa local government area of Kaduna State as it affects the wellbeing of the people in improving their standard of living vis-à-vis poverty eradication. Purposeful and simple random sampling technique was used to sample 220 respondents in the study area. Data was collected from the respondents using the interview schedule and a total of 179 questionnaires were used for the analysis. The principal results of the study reveal the failure of poverty alleviation programmes with special reference to NAPEP in Giwa local government area. Hence this study therefore recommends that NAPEP as an agency of the government with the sole aim of coordinating all poverty alleviation efforts in the country should work in harmony with other ministries and agencies that are stakeholders in the fight against poverty; the provision of credit facilities and skills training should be one of the central focus in poverty eradication and Government should adopt a holistic approach to poverty alleviation in the country.